GENOTIPE PADI LOKAL ASAL BENGKALIS PROVINSI RIAU YANG TOLERAN CEKAMAN ALUMINIUM - Endah Budi Lestari; Dewi Indriyani Roslim; Herman Herman (UIR Press, 2014)
The major problem in acid soils is aluminium toxicity that can harm the rice plant roots. The objective of this study is to identify of Al-tolerant local rice genotypes from Bengkalis, Riau Province. Plant materials tested were four local rice genotypes from Desa Bantan Air, Kecamatan Bantan, Kabupaten Bengkalis, Riau Province, i.e., Amat Candu, Sadani, Solok, dan Yamin. Grogol variety was used as an Al-tolerant rice variety, while IR64 variety was used as an Al-sensitive rice variety. All genotypes/varieties were exposed to 12 ppm Al for 72 hours in nutrient culture, pH 4. Each treatment was repeated three times. Ten seedlings per genotype/variety were tested. Randomized Block Design was used in this research. The results showed that Yamin had the smallest PPA value (67%), followed by Grogol and Sadani (70%), Amat Candu (71%), Solok (72%), and IR64 (80%). Grogol and Sadani had same value of PPA and PAR, which demonstrated that both rice genotypes were tolerance to Al stress. It concluded that there were two Al-tolerant local rice genotypes from Bengkalis, such as Sadani and Yamin, while two others were Al-moderate, such as Amat Candu and Solok.